Disclosure : perspectives from four groups of participants - Go, Peter Paul L. (2000)
This study was conducted to see how disclosure is viewed and done from the perspectives of physicians, nurses, cancer patients and their families. Specifically, it aimed to: (a) decipher how disclosure of diagnosis, prognosis, treatment options and the disease progress are viewed by the four groups of participants; (b) to see if there are differences or similarities in the four groups' views and definition of disclosure; and (c) to see the importance of gender, civil status, family constellation, social support, educational attainment, profession, income bracket and level of religiosity on disclosure as a bioethical issue in health care.{{{{This investigation utilized a descriptive analytical research design. This was conducted in seven wards of a tertiary government hospital in Metro Manila. Using a non-probability sampling scheme, 83 participants comprising 12 physicians, 29 nurses, 23 cancer patients and 19 family members of the patients were the sample. Pre-tested open-ended questionnaires based on a given scenario were distributed to them to solicit their perspectives on disclosure. These were derived from these four groups of participants which provided the text discussion.{{{{Data were analyzed using percentage distribution and descriptive narration as disclosure, being a bioethical issue cannot be measured quantitatively. Results show that both parents and their families are desirous to know the totality of the malignancy encompassing diagnosis, prognosis, the available treatment options and the progress of the diasease. The attending physician is identified as the appropriate person to do the disclosure due to his/her vast knowledge and expertise on the management of the diasese. Nurses, on the other hand, are viewed as important ...
Thesis (Master of Arts in Nursing) -- University of the Philippines Manila
Keywords: Informed consent; Medical ethics; Patient education; Right to die